Techno-economic evaluation of an element-scale forward osmosis-reverse osmosis hybrid process for seawater desalination - Im, Sung Ju; Jeong, Sanghyun; Jeong, Seongpil; Jang, Am (ELSEVIER, 2020)
The forward osmosis (FO)-reverse osmosis (RO) hybrid process is gaining attention in the desalination market because it can purify diluted seawater and the RO unit functions at low pressure conditions, resulting in a reduced total operational cost. However, FO element configuration affects the process performance, minimum flow rate, inlet pressure, product capacity, and draw solution (DS) dilution rate. Moreover, economic evaluation of the FO-RO hybrid process in the Middle East, which is the largest seawater desalination market, is required to obtain representative results. Realistic economic evaluation can be achieved with a real-performance database (DB) and specific assumptions. In this study, a techno-economic evaluation of the FO-RO hybrid process was conducted using real element-scale FO DB and simulation DB, and the results were compared with those of a stand-alone two stage RO process. Spiral wound FO (SWFO) and plate and frame (PFFO)-RO hybrid processes were more economical by 8.84% and 3.73%, respectively, when compared to two-stage RO. In the Middle East, the total cost of SWFO-RO was 45.1 M$ lesser than that of PFFO-RO due to its higher water flux and DS dilution rate. Therefore, the FO-RO hybrid process has high economic potential in the Middle East and elsewhere.
Keywords: WASTE-WATER REUSE; LIFE-CYCLE; OSMOTIC DILUTION; MEMBRANE; SYSTEM; COST; OPTIMIZATION; FEASIBILITY; PERFORMANCE; CHALLENGES